Use of Ad Texts in Teaching Listening and Writing Skills - Ali Göçer; Akife Kurt (Educational Academic Research)
Ad text is an important information and persuasion tool. Advertising texts can be found in traditional or digital media such as newspapers, magazines, radio, e-mail, and social media. Advertising texts are not only a means of promoting a product or service, but also a means of conveying cultural and social messages. Elements such as text, icons, images, and music in the ad text complement each other and create a meaning. Combining these elements to attract the target audience's attention and effectively convey the message plays a critical role in the advertisement's success. Thus, it takes its place in the universe of meaning of the listener/viewer. Especially considering the increasing advertising intensity in the recent period when technology has developed, it is a fact that children are exposed to advertising messages. This situation further increases the importance of creating a critical perspective and media literacy skills. Ad text is a type of text that is used in both listening/monitoring and writing skills in the Turkish Curriculum (2019). This study aims to show that advertising texts can provide a theoretical framework for the acquisition of critical listening/watching and creative writing skills, based on the achievements in Turkish language lessons. In the study, theoretical information about the advertisement text was presented and activities suitable for listening/watching and writing skills were designed in the light of this information. As a result of the study, some suggestions were made for the effective and active use of advertising text in Turkish lessons.